Structure and Reactivity of Metals in Zeolite Materials (Structure and Bonding,, 2018)
This volume provides the reader with the most up-to-date and relevant knowledge on the reactivity of metals located in zeolite materials, either in framework or extra-framework positions, and the way it is connected with the nature of the chemical environment provided by the host. Since the first report of the isomorphous substitution of titanium in the framework of zeolites giving rise to materials with unusual catalytic properties, the incorporation of many other metals have been investigated with the aim for developing catalysts with improved performance in different reactions. The continuous expansion of the field, both in the variety of metals and zeolite structures, has been accompanied by an increasing focus on the relationship between the reactivity of metal centers and their unique chemical environment. The concepts covered in this volume are of interest to people working in the field of inorganic and physical chemistry, catalysis and chemical engineering, but also for those more interested in theoretical approaches to chemical reactivity. In particular the volume is useful to postgraduate students conducting research in the design, synthesis and catalytic performance of metal-containing zeolites in both academic and application contexts.